Chapter Fragmenta poetarum Latinorum in papyris reperta: Occidente ed Oriente, testi e contesti - Scappaticcio, Maria Chiara (Beiträge zur Altertumskunde, 2016)
The volume collates ten studies that confront the main issues of the research on Roman poetic fragments: textual criticism and interpretation, new additions to the corpus, authorship, prosody and colometry, literary genre, and the connection between quotation and context. The editors' methodological introduction also provides an up-to-date review of the scholarship on the subject, that aims to supplement Blänsdorf`s bibliography.